The Influence of Price, Product Quality, and Promotion on Consumer Purchase Intention in Lamongan Ikat Weaving Products in the Modern Market - Agus Prasetiyo; Andry Herawati; Galuh Ajeng Ayuningtiyas (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
Lamongan ikat weaving is a local cultural heritage that has artistic and cultural value, as well as high economic potential. However, in the increasingly competitive modern market, this traditional product faces challenges in attracting consumer interest. This study aims to analyze the influence of price, product quality, and promotional activities on consumer purchase intentions of Lamongan ikat weaving marketed through modern channels, such as shopping centers, fashion boutiques, and e-commerce platforms. The study used a quantitative approach with data collection through a Likert scale questionnaire that has been tested for validity and reliability. A total of 100 respondents were obtained using a cluster random sampling technique. Data analysis was carried out using multiple linear regression, supported by classical assumption tests and hypothesis testing through partial (t-test) and simultaneous (F-test) tests. The results showed that the variables of price, product quality, and promotion simultaneously had a significant effect on consumer purchase intentions (p = 0.000). However, only product quality was proven to have a significant effect (p = 0.000), while price and promotion did not show a significant effect (p = 0.214 and p = 0.257, respectively). The adjusted R² value of 0.379 indicates that 37.9% of the variance in consumer purchase intention can be explained by the three independent variables, while the remainder is influenced by other factors outside this study. This finding confirms that product quality is the dominant factor driving consumer purchase intention for Lamongan ikat weaving. Therefore, business actors are advised to prioritize quality improvement through quality control and design innovation, as well as developing more targeted, creative promotional strategies that are in line with the preferences of modern market consumers. Thus, Lamongan ikat weaving will not only be able to maintain its existence but also have a great opportunity to develop in the contemporary creative and fashion industries.